Morphophysiology characterization of Araucaria angustifolia (Bertol.) Kuntze for identification of matrix trees - Pires, Victória Campos Monteiro [UNESP]; Guimarães, Cristiane Carvalho [UNESP]; de Moraes, Thatiele Pereira Eufrazio; Dionisio, Luiz Fernandes Silva; de Moraes, Cristiano Bueno; da Silva, Edvaldo Aparecido Amaral [UNESP] (Universidade Federal de Santa Maria, 2024)
The forest fragmentation and uncontrolled exploration of the Araucaria angustifolia led to the inclusion of this species in the list of Brazilian species threatened with extinction, which culminated in the need to identify parent trees for seed collection and seedling production. Thus, the objective of this work was to describe the morphological characteristics of the different plant materials of Araucaria angustifolia, as well as evaluate the physiological quality of the seeds for the identification of matrix trees for collection in the study area. Each tree was considered a distinct matrix, and initially, the biometric characterization of cones and seeds was performed. Subsequently, the evaluation of similarity was defined using the Euclidean distance method and the “single linkage method”. The physiological potential of the seeds was determined through tests of germination, germination speed index, dry mass and seedling length. The vegetative materials studied presented variation in the biometric data, and for the seeds, there was also a difference in the physiological characteristics. The matrices 1, 5 and 18 stood out positively from the others and the evaluation of biometrics, germination, emergence and seedling length was considered efficient for the determination of the seed’s physiological quality. Such information can help in future management programs in Araucaria forest areas in the region.
Caracterização morfofisiológica de Araucaria angustifolia (Bertol.) Kuntze para identificação de árvores matrizes
Keywords: Biometrics; Physiology; Pine cone; Seeds